Virtual Aquascape for Users Utilizing Augmented Reality: Aquascape Virtual Untuk Pengguna Menggunakan Augmented Reality - Aini, Della Swastika Nur; Dijaya, Rohman; Rahmawati, Yunianita (Universitas Muhammadiyah Sidoarjo, 2023)
Aquascape is the art of arranging plants in water. The large number of complaints from aquascape buyers were not up to expectations, causing sellers to have difficulty in setting an example of an orderable aquascape, so researches created an aquascape application system to increase their promotional activities with augmented reality technology accessible through smartphone. One uses the methode MDLC (Multimedia Development Life Cycle). As a result, the application can implement a markless augmented reality to display 3D objects in real time with the help of a camera on a smartphone or a trilib feature by importing 3D object files found on file managers on a smartphone. User can easily provide the desired aquascape example of the aquascape application.